Designing Android-Based Augmented Reality as an ICT Learning Media - irva nurjaman; Demmy Bhakti; Tetep Dr., M.Pd (Institut Pendidikan Indonesia, 2021)
Augmented Reality can be defined as a real environment in which virtual objects are added with the integration of computer technology. This technology can present interesting interactions for the user, because with this technology the user can feel virtual objects as if they actually exist in a real environment. This study will include AR technology to create learning media, so that the use of practicum time is maximized and allows students to understand and recognize computer networks. Research and application development using the Waterfall model provides a sequential or sequential software lifeflow approach starting from analysis, design, coding and testing. Testing the application using Black Box Testing and Augmented Reality Application Questionnaire for Network Devices went well. Minimum specifications of Augmented Reality Applications Network Devices with Operating System (OS) Android v6.0 Marshmallow, 2.1 GHz Deca-core Processor, 12 MP Camera, 2 GB Ram and 32 GB Memory with application specifications can run well.